Freeloader Enterprise / Mohd Samsudin Abdul Hamid... [et al.] - Abdul Hamid, Mohd Samsudin; Azizan, Dzulkhairy; Ab Kadir, Wafiuddin Nasrullah; Abd Rahman, Mohd Azfar (2006)
Freeloader Enterprise is the company that involved in information technology business. This company is under the partnership condition that consists of 5 partners and will establish on 19 January 2007. A part from that, the capital of our business is 20% from the shareholders and 80% from the loan application. Our capital loan is from Bank Islam Malaysia Berhad. Basically, our company main activities are internet café, computer classes, and hardware selling. Our company is located at No 17 & 18, Jalan Penjara, Perlis Indera Kayangan. We believe that this location is the strategic place that we can establish our business. A part from that, there have 4 department in our company which is administration department, marketing department, operation department, and financial department. Each department has their job responsibilities that need to follow for develop our company.